Remote Control of Variable Angle Displays in Industrial Facilities with Mobile AR - FEYZİOĞLU, AHMET (My University, 2022)
Installation systems used in production are usually placed under the roof of the plant. Production system and devices working on the ground; Requirements such as electricity, compressed air, normal ventilation, oil, hot water and water vapor are provided through the output modules of the installation systems. There are indicators on these modules that show the pressure, temperature and similar parameters of the module. During the periodical maintenance periods, the indicators of modules are checked one by one by the maintainer. The difficulty with this process is that modules are high and inaccessible areas. Also, in order to interpret the checked indicator values and to determine whether the indicator works correctly or not, it may be necessary to evaluate it with other indicator connected to that system. Indicators are monitored electronically with automation systems and can be interpreted with scada systems. Although installations are equipped with sensors and monitored with scada systems, it may be necessary to verify the sensors from time to time, and sometimes back up with non-digital displays due to the software side that can be disabled for a while. Indicators are monitored by maintainers. For reasons, it is necessary to read and interpret data in a way that will not hinder production and risk the safety of property and life in order to obtain and verify data from hard-to-reach indicators. In this direction, a mobile application has been designed that can work on a mobile phone that everyone has, and reads and identifies data remotely using augmented reality (AR) techniques. This application can receive and compare digital data from the SCADA system via the facility's network. If there is no network, it can work by comparing the technical values previously loaded to the software and interpreting it with other sensors read when necessary.
Keywords: Augmented reality; Busbar; Busway; Installation indicators; Mobile application